Artesunate-amodiaquine efficacy in Congolese children with acute uncomplicated falciparum malaria in Brazzaville - Ndounga Mathieu; Mayengue Pembe Issamou; Casimiro Prisca Nadine; Loumouamou Dieudonné; Basco Leonardo K; Ntoumi Francine; Brasseur Philippe (Malaria Journal, 2013)
Abstract Background Congo-Brazzaville adopted artemisinin-based combination therapy (ACT) in 2006. Artesunate-amodiaquine (AS + AQ) and artemether-lumefantrine are the first-line and second-line anti-malarial drugs to treat uncomplicated Plasmodium falciparum malaria, respectively. The baseline efficacy of AS + AQ was evaluated from February to August 2005 in patients living in Brazzaville, the capital city of the Republic of Congo. Methods One hundred and ninety-seven patients (96 ≤5 years old and 101 >5 years old, including adults) were recruited in a non-randomized study, treated under supervision with AS + AQ, and were followed up for 28 days in accordance with the 2003 World Health Organization protocol. Plasmodium falciparum recrudescent isolates from day 7 to day 28 were compared to pretreatment isolates by polymerase chain reaction (PCR) to distinguish between re-infection and recrudescence. Results The overall efficacy of AS + AQ after PCR correction on day 28 was 94.4%. An adequate clinical and parasitological response was observed in 94.3% and 94.4% of children aged ≤5 years old and those aged >5 years old (including adults), respectively. The main reported adverse events were dizziness, vomiting, diarrhoea, pruritus, headache, anorexia, and abdominal pain. Conclusion This study has shown the high efficacy of AS + AQ in Congolese patients of all ages with acute uncomplicated falciparum malaria and serves as the baseline efficacy and tolerance of this ACT in Brazzaville.